The Influence of Service Quality towards Customer Satisfaction on Garuda Airline of Yogyakarta International Airport on Pandemic covid-19 - Adib Susilo; Muhammad Kurnia Rahman Abadi; Abdullah Sahroni; Mufti Afif (Universitas Darussalam Gontor, 2022)
This research aimed to investigate the service quality provided by Garuda Indonesia Airlines at Jogjakarta international Airport on customer satisfaction. 200 questionnaire was deployed which return and able to analyze about 142 questionnaire. Multiple Regression analysis employed to analyze the relationship between service quality dimension (tangible, reliability, responsiveness, and assurance) and customer satisfaction. The result shows that simultaneously all independents variable has a positive impact on dependent variable. Meanwhile, partially tangible and reliability has positive significant influence on customer satisfaction while responsiveness and assurance is insignificant to customer satisfaction. The R2 shows that 0.487 means 48.7% of dependent variable was explained and influenced by independent variables while the rest of it about 51.3% was influenced by another variable that not included in this research.